F(R)-gravity from Killing tensors. (11th March 2016) - Paliathanasis, Andronikos
Abstract: We consider f ( R )-gravity in a Friedmann–Lemaître–Robertson–Walker spacetime with zero spatial curvature. We apply the Killing tensors of the minisuperspace in order to specify the functional form of f ( R ) and for the field equations to be invariant under Lie–Bäcklund transformations, which are linear in momentum (contact symmetries). Consequently, the field equations to admit quadratic conservation laws given by Noether's theorem. We find three new integrable f ( R )-models, for which, with the application of the conservation laws, we reduce the field equations to a system of two first-order ordinary differential equations. For each model we study the evolution of the cosmological fluid. We find that for each integrable model the cosmological fluid has an equation of state parameter, in which there is linear behavior in terms of the scale factor which describes the Chevallier, Polarski and Linder parametric dark energy model.